Smart Antibacterial Surfaces Established by One‐Step Photo‐Crosslinking. Issue 24 (31st October 2017) - Dong, Yishi; Wang, Peixi; Wei, Ting; Zhou, Tao; Huangfu, Mengge; Wu, Zhaoqiang
Abstract: Chemical modification of surfaces is recognized as efficient strategies to prevent bacterial contamination and the associated infection. Herein, a novel ionic liquid derivative 1‐(((4‐benzoylbenzoyl)oxy)methyl)‐3‐methyl‐1 H ‐imidazol‐3‐ium bromide (BMI) containing benzophenone moieties is developed to act as both a photoreactive cross‐linker and an antibacterial agent. BMI can rapidly and efficiently form a "smart" antibacterial film on a variety of substrate surfaces in 2 min under mild UV irradiation. The modified surfaces show highly antibacterial activity, achieving more than 99% bacterial killing efficiency against Gram‐positive Staphylococcus aureus and Gram‐negative Escherichia coli using live/dead staining methods. In addition, the BMI‐modified surfaces can release ≈97% of the killed bacteria via ion‐exchange of hexametaphosphate (PP 6− ) anions and can regenerate bactericidal properties over three cycles. Moreover, in vitro cytocompatibility tests indicate that the BMI‐modified surfaces have good biocompatibility. Thus, it can be concluded that cross‐linked BMI layers provide a practical and convenient approach for the fabrication of "smart" antibacterial surfaces. Abstract : The novel ionic liquid derivative (1‐(((4‐benzoylbenzoyl)oxy)methyl)‐3‐methyl‐1 H ‐imidazol‐3‐ium bromide) can rapidly and efficiently form a "smart" antibacterial film on a variety of substrate surfaces by one‐step photo‐crosslinking in 2 min under atmospheric conditions. The modified surfaces show highly antibacterial activity against both Gram‐positive and Gram‐negative bacteria and can be regenerated over three cycles.